Day 2 Tue, November 03, 2020 2020
DOI: 10.4043/30196-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advances Towards a Comprehensive Model of Laser-Rock Interaction

Abstract: Laser applications provide unique advantages to applications in discovery, recovery, and production of hydrocarbons. A comprehensive numerical model would enable prediction, optimization, increase efficiency, enhance control, and further innovation. This work reviews the modeling methods, discusses key variables and physics, presents results, and introduces innovative solutions that make use of machine learning and artificial intelligence to solve an inherently multi-scale and multi-physics problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[42][43][44][45][46][47][48] In these works, neural networks are used to build constitutive models based on laboratory tests. 49,50 Only one research work was found that proposes a numerical method based on machine learning. 51 In this work, a model reduction is proposed to predict displacements and stresses combining "proper orthogonal decomposition" (POD) and "multi-output support vector machine" (MSVM).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45][46][47][48] In these works, neural networks are used to build constitutive models based on laboratory tests. 49,50 Only one research work was found that proposes a numerical method based on machine learning. 51 In this work, a model reduction is proposed to predict displacements and stresses combining "proper orthogonal decomposition" (POD) and "multi-output support vector machine" (MSVM).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…By using this combination, the search found papers that study the training of neural networks to perform inverse analysis, 39–41 which uses in loco measurements to build meta models for the massive 42–48 . In these works, neural networks are used to build constitutive models based on laboratory tests 49,50 . Only one research work was found that proposes a numerical method based on machine learning 51 .…”
Section: Systematic Literature Reviewmentioning
confidence: 99%